Filipino nurses as enablers of the future welfare state: the global commodity chains of producing racialized care labour for ageing Finland - Kettunen, Pauli; Pellander, Saara; Tervonen, Miika (Edward Elgar Publishing, 2022)
In the current policy environment in Finland, labour migration is portrayed as a solution for the sustenance of the ageing welfare state. However, foreign professional qualifications are generally less valued than those of native-born citizens, particularly for racialized migrants coming from outside the 'west'. Such devaluation of human capital is prevalent in nursing, where the menial basic care has turned into a 'migrant's job', whereas clinical work is left for those considered as 'natives'. In this chapter, we examine how the Filipino registered nurses' professional skills are systematically devalued, as they are recruited to Finnish eldercare as enablers of the future welfare state. We demonstrate how Filipino nurses are produced as highly skilled export commodities in the Philippines, only to be deskilled upon entry to the Finnish labour markets as embedded in the EU. In conclusion, we outline policy measures that would make the transnational recruitment processes more ethical.